The stress-strain and strength characteristics of Portaway Sand - Wang, Jun (2005)
Despite the large number of modifications proposed to the standard Cam-clay models over the last three decades, the critical state concept has been much less successful for modelling sand behaviour. This thesis is concerned with understanding the stress-strain and strength characteristics of Portaway sand, a quartz sand, and the validity of several recently developed critical state models formulated in terms of the state parameter concept.